Facilitating writing seminars: Beyond shutting up and writing down - Høgetveit, Åsne Ø. (Septentrio Conference Series, 2021)
How can the University Library better accommodate for students and faculty who need practical help with getting their writing done and develop their work habits? For many involved in academia, students and staff alike, the crucial task of writing is also one of the most challenging. People struggle to get past the first sentence, because it is not quite perfect yet; it is difficult to find the time; they do not feel inspired to write right now, etc. A possible help for some is to participate in writing seminars. Such seminars can take on various forms, depending on the needs of the participants and the circumstances around them. Writing seminars provide a supporting framework by making writing a more collective act. Participants find that they are both held accountable and inspired by their peers in the seminar. Considering how simple and easy it can be to set up and arrange such seminars it is no wonder university libraries, writing centres etc. do this. But can we go beyond simply setting a time, booking a room, and posting a note about it? Based on my experience as a writing seminar participant and now University Library staff and seminar organiser I want to develop the way we facilitate writing seminars. Organising our own seminars limit the participants to a set time and location of our choosing, and have limited outreach. In addition, hosting a two hours seminar, say, weekly, may not be the best use of staff working hours. Instead, I would like to develop a writing seminar service where the library helps people who want to set up their own writing groups. This way we can reach more people and help establish customised writing seminars.